Peran Dinas Pengendalian Penduduk Pemberdayaan Perempuan dan Perlindungan Anak dalam Menangani Kasus Kekerasan pada Perempuan dan Anak di Kabupaten Sumba Barat - Vinca Debora Rara Dewanti Kalemodjo; Nursalam Nursalam; Delila A. N. Seran (Jurnal Ekonomi Manajemen Akuntansi, 2026)
The increasing incidence of violence against women and children requires an active and effective role of public organizations in providing sustainable protection. This study aims to analyze the role of the Population Control, Women’s Empowerment, and Child Protection Office (DP5A) of West Sumba Regency in handling cases of violence against women and children. The research employs a descriptive qualitative approach. Data were collected through interviews, observations, and document analysis from purposively selected informants and analyzed using data reduction, data presentation, and conclusion drawing, supported by source and technique triangulation. The findings indicate that DP5A has performed its facilitative, educational, representative, and technical roles; however, their implementation has not been optimal. Major obstacles include limited facilities such as the absence of a permanent safe house, inadequate operational infrastructure, limited human resource capacity, underutilization of information technology and digital media, as well as cultural and administrative constraints. This study concludes that institutional strengthening, capacity building of personnel, optimization of technology utilization, and enhanced cross-sector collaboration are essential to improve the effectiveness of protection for women and children at the local level.